EFFECT OF COMPACTED COMPOUND SLOW RELEASE FERTILIZER TO IMMATURE OIL PALM GROWTH AND YIELD ON XANTHIC HAPLUDOX, IN MERANGIN, JAMBI - WIGENA, I GEDE PUTU; PURNOMO, J.; TUHERKIH, E.; SALEH, A. (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2006)
Oil palm is one of promoted plantation commodity that is developed intensively by the government. This phenomena need to be supported by an appropriate management mainly the fertilization aspects to maintain its productivity at high level. Field experiment has been conducted to test the effect of the compacted compound slow release fertilizer, formulated in stick fertilizer, to immature oil palm growth and fruit bunches production on Xanthic Hapludox from 2003 to 2005. Seven fertilization treatments, namely farmer?s practice (A); recommended fertilization (B); controll (C); 1 fertilizer stick/trunk (D); 2 fertilizer sticks/trunk (E); 3 fertilizer sticks/trunk (F); and 2 fertilizer sticks combined with foliar fertilizer (Fosfo N)(G) have been tested on the experiment. All treatments were arranged in randomize complete block design with three replications. The result showed that the tested fertilizer could improve oil palm growth and increased fruit bunches production significantly. The highest yield was provided by 3 fertilizer stick/trunk (G) with growth scoring 90.30% and 31.43 kg of fruit bunches/trunk. This yield was significantly different with all others tested treatment, except recommended treatment (B) with growth scoring and fruit bunches were 87.30% and 30.57 kg/trunk/month, respectively. Compared to the recommended treatment, the application of the tested fertilizer could decrease the total fertilizers required by the farmers due to the increasing of fertilization efficiency about 50-60%. Based on nutrients dynamic and number of fertilizers required by oil palm, the existing recommended fertilization should be changed in order tomaintain nutrient balance in the soil. The proposed changes of recommended fertilization is by increasing of potassium dosage because oil palm absorp potassium at the highest number from the soil. Besides that, sulfur should be applicated due to the higher absorption by the crop from the soil, whereas the highly weathered soil has lower capacity in supplying sulfur for crop growth so that sulfur is adsorp extensively from the soil and causes imbalance nutrient in the soil.